Developmental stages and gut microenvironments influence gut microbiota dynamics in the invasive beetle Popillia japonica Newman (Coleoptera: Scarabaeidae). (21st October 2019) - Chouaia, Bessem; Goda, Nizar; Mazza, Giuseppe; Alali, Sumer; Florian, Fiorella; Gionechetti, Fabrizia; Callegari, Matteo; Gonella, Elena; Magoga, Giulia; Fusi, Marco; Crotti, Elena; Daffonchio, Daniele; et al.
Summary: Popillia japonica Newman (Coleoptera: Scarabaeidae) is a highly polyphagous invasive beetle originating from Japan. This insect is highly resilient and able to rapidly adapt to new vegetation. Insect‐associated microorganisms can play important roles in insect physiology, helping their hosts to adapt to changing conditions and potentially contributing to an insect's invasive potential. Such symbiotic bacteria can be part of a core microbiota that is stably transmitted throughout the host's life cycle or selectively recruited from the environment at each developmental stage. The aim of this study was to investigate the origin, stability and turnover of the bacterial communities associated with an invasive population of P. japonica from Italy. Our results demonstrate that soil microbes represent an important source of gut bacteria for P. japonica larvae, but as the insect develops, its gut microbiota richness and diversity decreased substantially, paralleled by changes in community composition. Notably, only 16.75% of the soil bacteria present in larvae are maintained until the adult stage. We further identified the micro‐environments of different gut sections as an important factor shaping microbiota composition in this species, likely due to differences in pH, oxygen availability and redox potential. In addition, P. japonica also harboured a stable bacterial community across all developmental stages, consisting of taxa well known for the degradation of plant material, namely the families Ruminococcacae, Christensenellaceae and Lachnospiraceae. Interestingly, the family Christensenallaceae had so far been observed exclusively in humans. However, the Christensenellaceae operational taxonomic units found in P. japonica belong to different taxonomic clades within this family.